Die Rechtsstellung der Frau als Gattin und Mutter : Geschichtliche Entwicklung ihrer persönlichen Stellung im Privatrecht bis in das achtzehnte Jahrhundert - Bartsch, Robert, 1874-1955 (Historische Quellen zur Frauenbewegung und Geschlechterproblematik ;, 1903)
A history of the legal conditions governing wives and mothers from Roman times until the 18th century. Each chapter is preceded by bibliographical listings, and there is a lengthy index of quoted sources.